Correlation estradiol levels and physical activities with lipid profile levels of premenopausal women, in Padang city, Indonesia - Hafizah, Hafizah; Afriwardi, Afriwardi; Anggraini, Fika Tri; Sulastri, Delmi (International Journal of Research in Medical Sciences, 2019)
Background: In premenopausal women, low estradiol levels and lack of physical activity can result in dyslipidemia. Dyslipidemia is a risk factor for coronary heart disease (CHD). The incidence of CHD occurs a lot in premenopausal age compared to productive age, the percentage of women who experience higher CHD than men. Objective was to determine the correlation of estradiol levels and physical activity with lipid profiles in premenopausal women in Padang City. Methods: This research was carried out in Padang City. The study was observational, cross-sectional design. The study sample was 79 premenopausal women. Estradiol levels were assessed by the ELISA method, physical activity was assessed by an international physical activity (IPAQ) questionnaire, lipid profiles were assessed by colorimetric enzymatic methods. Correlation of estradiol levels with lipid profile levels were analyzed using the Pearson correlation test. Correlation of physical activity with lipid profile level using the ANOVA test. Results: The mean estradiol level of respondents was 144.68pg/ml, the mean physical activity of respondents is heavy physical activity as much as 41.8%, the mean cholesterol level of respondents was 194.76mg/dl, the mean triglyceride level of respondents was 118.75mg/dl, the mean LDL cholesterol level of respondents was 120.64mg/dl, the mean HDL cholesterol level was 53.18mg/dl. Conclusions: There were significant correlation between estradiol levels with triglyceride levels and LDL cholesterol. There was significant correlation physical activity with total cholesterol levels and triglyceride levels. There was no correlation between estradiol levels with total cholesterol and HDL cholesterol. There was no correlation physical activity with LDL cholesterol and HDL cholesterol.